Potency of honey as antibacterial agent against multiple antibiotic resistant pathogens evaluated by different methods - Aween M.M.; Hassan Z.; Emdakim M.M.; Muhialdin B.J.; Nur Huda Faujan (Science Publications, 2024)
Indexed by Scopus